AB0249 POSITIVE EFFECT OF ANTIRHEUMATIC THERAPY ON THE COURSE OF CHRONIC HEART FAILURE IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS. (13th June 2020) - Kirillova, I.; Novikova, D.; Popkova, T.; Gorbunova, Y.; Markelova, E.; Volkov, A.
Abstract : Background: Objectives: to evaluate the effect of antirheumatic therapy according to the "treat to target" strategy on the course of chronic heart failure (CHF) in patients with early RA. Methods: The study included 22 patients CHF with valid diagnosis of RA (criteria ACR / EULAR, 2010), 17 (77%) of women, median (Me) age - 60 years, Me disease duration - 7 months; IgM seropositive for rheumatoid factor 10 (45%) and / or antibodies to the cyclic citrulline peptide 22 (100%), DAS28-5.6 [4, 8;6, 5]. CHF verified in accordance the recommendations for the diagnosis and treatment of CHF Society of Specialists in Heart Failure (2013). The concentration of NT-proBNP was determined by electrochemiluminescence. For all patients was started methotrexate (MT) therapy with a rapid increase in the dose to 30 mg per week subcutaneously. If the MT was not effective enough, after 3 months a biological Disease-Modifying Anti-Rheumatic Drug (bDMARDs) was added to the therapy, predominantly TNF-alpha inhibitors. After 18 months, 10 (45%) patients were in remission and low disease activity, 6 (60%) of patients underwent MT therapy in combination with bDMARDs. Results: In baseline CHF with preserved EF was revealed in 21 (95%) patients, in 1 patient - CHF with reduced EF. After 18 months there was a positive dynamics of improvement of clinical symptoms, echocardiographic indicators (decrease the size of the left atrium (LА) and the index of end-systolic volume of LА, IVRT, E' LV), diastolic function of the left ventricle (LV). There was no decompensation of CHF. LV diastolic function normalized in 7 (32%) patients who reached the target level of blood pressure, remission (n = 5) and low (n = 2) disease activity, mainly in the treatment of MT and bDMARDs. In patients with RA and CHF, the level of NT-proBNP decreased from 192.2 [151.4; 266.4] to 114.0 [90.4; 163.4] pg / ml (p <0.001), normalized in 16 of 22 (73%) patients (p <0.001) with remission or low RA activity. In 5 (22%) patients, the clinical manifestations of CHF regressed, LV diastolic function and NT-proBNP level normalized. Conclusion: In patients with early RA and CHF anti-rheumatic therapy improves the clinical course of CHF. There were an improvement in the clinical course of CHF, diastolic function of the left ventricle and a decrease in NT-proBNP. Disclosure of Interests: None declared